Blood Protein Polymorphism on Javanese Fat Tailed Sheep and Javanese Thin Tailed Sheep - Irene (Irene); S. Wuwuh; Sutopo (Sutopo); B. Sutiyono (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy